2021
DOI: 10.4103/ijciis.ijciis_194_20
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in ventilated patients with coronavirus disease-2019 pneumonia: A single-center retrospective study

Abstract: Background: Acute kidney injury (AKI) is repeatedly observed in ventilated critically ill patients with coronavirus disease-2019 (COVID-19) pneumonia. This study aimed to determine the incidence, risk factors, and consequences of AKI in the ventilated critically ill adult patients with COVID-19 pneumonia. Methods: This retrospective study included all the ventilated critically ill adult patients with COVID-19 pneumonia from March 1, 2020, to June 1, 2020. Data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
11

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 57 publications
0
1
0
11
Order By: Relevance
“…Todos os estudos incluídos foram publicados em língua inglesa, entre 2020 e 2022, desenvolvidos na América do Sul (16)(17)(18)(19) e América do Norte, (20)(21)(22)(23)(24)(25)(26)(27) Ásia, (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) Europa, (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53) África (54) e Oriente Médio. (55)(56)(57)(58) O país com maior número de publicações sobre LRA associada à COVID-19 foi a China, contemplando 27,3% (n = 12) dos artigos. (31)(32)(33)(34)(35)(36)…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Todos os estudos incluídos foram publicados em língua inglesa, entre 2020 e 2022, desenvolvidos na América do Sul (16)(17)(18)(19) e América do Norte, (20)(21)(22)(23)(24)(25)(26)(27) Ásia, (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) Europa, (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53) África (54) e Oriente Médio. (55)(56)(57)(58) O país com maior número de publicações sobre LRA associada à COVID-19 foi a China, contemplando 27,3% (n = 12) dos artigos. (31)(32)(33)(34)(35)(36)…”
Section: Resultsunclassified
“…(55)(56)(57)(58) O país com maior número de publicações sobre LRA associada à COVID-19 foi a China, contemplando 27,3% (n = 12) dos artigos. (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) Todos os estudos foram observacionais, com predomínio de coorte 63,6% (n=28), (16,17,20,21,23,28,29,(31)(32)(33)(35)(36)(37)(38)40,41,(43)(44)(45)(46)(51)(52)(53)(55)(56)(57)(58)(59) 77,3% (n = 34) retrospectivos (16)(17)(18)20,21,(24)...…”
Section: Resultsunclassified
See 2 more Smart Citations
“…The complication often occur along the course of COVID-19 hospitalization and is associated with increased illness severity, duration of stay, and poor prognosis [ 52 ]. Elkholi, et al found that AKI occurred in 65.1% of mechanically ventilated COVID-19 patients, and it was associated with significantly higher mortality [ 53 ]. Given that the data is from a registry and the study is retrospective, determining the cause-effect relationship is outside the scope of our study, and further studies are need to understand this aspect.…”
Section: Discussionmentioning
confidence: 99%